PENGARUH CITRA MEREK, HARGA, DAN DESAIN PRODUK TERHADAP PENGAMBILAN KEPUTUSAN PEMBELIAN SEPATU NIKE AIR JORDAN DI UNIVERSITAS KOTA BANJARMASIN - Naufal, Muhammad; Zamrudi, Zakky; Mursanto, Mursanto (JURNAL KINDAI, 2025)
This study aims to analyze the influence of brand image, price, and product design on purchasing decisions of Nike Air Jordan shoes among university students in Banjarmasin City. A quantitative approach with a survey method was employed, involving 100 students who were users or potential buyers of Nike Air Jordan products. Data were analyzed using multiple linear regression to examine the effect of independent variables on purchasing decisions. The results indicate that brand image, price, and product design simultaneously have a significant effect on purchasing decisions. However, partially, only brand image shows a positive and significant influence, while price and product design do not have a significant individual effect. These findings suggest that brand image is the dominant factor influencing students’ purchasing decisions, although the combined effect of all variables remains important. Keywords: brand image, price, product design, purchasing decision